Cardiac sarcoidosis: is early diagnosis possible? Case report - D. N. Antipushina; A. A. Zaitsev; P. G. Shakhnovich; S. A. Chernov; S. I. Kurbanov; D. N. Kazantsev (Кардиоваскулярная терапия и профилактика, 2023)
Cardiac involvement in sarcoidosis is difficult to diagnose due to the asymptomatic course in 95% of cases, the inaccessibility and low information content of a heart biopsy, the absence of pathological disorders in routine examination methods or their non-specificity. At the same time, it is cardiac sarcoidosis, along with damage to the nervous system, that is the main cause of mortality in sarcoidosis. Early diagnosis is of decisive importance for preventing complications associated with heart involvement and choosing the right treatment tactics. The positron emission tomography-computed tomography (PET-CT) is a method that can help the doctor in assessing the prevalence of sarcoidosis and verifying latent localizations in patients with a morphologically confirmed disease. The article describes a case of the use of PET/CT for the diagnosis of cardiac sarcoidosis.